Pengaruh Pemahaman Akuntansi, Pemanfaatan Sistem Informasi Akuntansi dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan di Bank Perkreditan Rakyat (Bpr) Se-Kecamatan Mengwi - Irayani, Ni Putu Nita; Putra, Cokorda Gde Bayu; Yuliantari, Ni Putu Yeni (Hita Akuntansi dan Keuangan, 2024)
The motive of monetary statements is to offer pertinent information about the economic repute and all transactions made by means of a reporting commercial enterprise within a reporting length. The prpose of thsi observe is to study how intetrnal manipulate systems, accounting statistics structures, and accounting expertise affect the quality of financial reviews produced by using BPR in the Mengwi District. The research became conducted at BPR inothe course of the Mengwi District. The sampling approach used purposive sampling and obtained 86 employees who prepared financial reviews. The statistics evaluation method makes use of more than one linear regression, device check, classical assumption check, and model feasibility test. The findings validated that internal manipulate mechanisms, accounting records machine use, and accounting knowledge all had a favorable and giant impact on the standard of financial reviews in BPR throughout the Mengwi District